Nonfatal Agricultural Injuries in Florida: Crop Production: AE580/AE580, 10/2022 - Francois, Joelle; Ward, Cassandra; Gorucu, Serap (EDIS, 2022)
This publication examines nonfatal injuries and illnesses among crop production workers in Florida. Written by Joelle Francois, Cassandra Ward, and Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2022.